2016
DOI: 10.1371/journal.pone.0158172
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Dynamics and Changes in Chemical Composition of Wheat Straw Residue under Anaerobic and Aerobic Conditions

Abstract: Soil aeration is a crucial factor that regulates crop residue decomposition, and the chemical composition of decomposing crop residues may change the forms and availability of soil nutrients, such as N and P. However, to date, differences in the chemical composition of crop straw residues after incorporation into soil and during its decomposition under anaerobic vs. aerobic conditions have not been well documented. The objective of the present study was to assess changes in the C-containing functional groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 49 publications
(77 reference statements)
4
35
0
Order By: Relevance
“…In a population consisting of 495 genotypes measured over two years, we found that genotype could explain 23% of variation in C emission and broad-sense heritability was 0.25. The substantial variation observed in this study for C emission across environments agrees with observations from studies of other species Yanni et al, 2011, Gao et al, 2016.…”
Section: Genotype Effects and Heritabilitysupporting
confidence: 89%
“…In a population consisting of 495 genotypes measured over two years, we found that genotype could explain 23% of variation in C emission and broad-sense heritability was 0.25. The substantial variation observed in this study for C emission across environments agrees with observations from studies of other species Yanni et al, 2011, Gao et al, 2016.…”
Section: Genotype Effects and Heritabilitysupporting
confidence: 89%
“…Eh changes occur more rapidly in flooded rice paddy fields in the presence of readily decomposable rice straw [32]. The lignin level in soybean stover (11.9%) is higher than in rice straw (7.3%) [33], and high lignin content slows the decomposition of organic matter [34]. Moreover, growing an upland crop in rotation with flooded rice can cause sufficient aeration of the soil to increase Eh periodically [30], which, in turn, may reduce CH4 emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Teixeira et al (2011) evaluated the decomposition and release of nutrients from the aerial part of millet and sorghum plants, found half-life (t½), 98 days for millet, and 96 days for sorghum. However, Gao et al (2016) evaluated the decomposition of wheat straw in anaerobic and aerobic conditions, found a longer half-life (t ½), 122 days, under anaerobic conditions, when compared to aerobic conditions, 73 days. In 2015, the remaining biomass was lower, which also had a shorter half-life (t ½).…”
Section: Biomassmentioning
confidence: 99%